High molecular weight adiponectin reduces glucolipotoxicity-induced inflammation and improves lipid metabolism and insulin sensitivity via APPL1-AMPK-GLUT4 regulation in 3T3-L1 adipocytes. (September 2019) - Pandey, Gautam Kumar; Vadivel, Sangeetha; Raghavan, Srividhya; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Gokulakrishnan, Kuppan
Abstract: Background and aims: Although the importance of adipokines in modulating the disease process of type 2 diabetes is well recognized, there is dearth of data on the specific role of high molecular weight adiponectin (HMW Ad) on insulin resistance and obesity. Therefore, we tested the effects of HMW Ad on glucolipotoxcity-induced inflammation and insulin resistance in 3T3-L1 adipocytes. Methods: 3T3-L1 adipocytes were subject to glucolipotoxicity with and without HMW Ad treatment. Real-time PCR and Western-blot experiments were performed to analyse gene and protein expressions, respectively. Lipolysis, adipored staining, and glucose uptake assay were performed to evaluate alterations in lipid and glucose metabolism. Results: Adipocytes subject to glucolipotoxicity showed significantly ( p  < 0.05) decreased mRNA expression of adiponectin, AdipoR2, GLUT4, and increased inflammation, lipid accumulation as well as lipolysis. Treatment with HMW Ad beneficially modulated lipid metabolism, reduced inflammation and improved glucose uptake in adipocytes. HMW Ad also beneficially regulated APPL1 and AMPK signaling in adipocytes. Silencing of APPL1 gene in adipocytes significantly reduced the effects of HMW Ad on pAMPK protein expression, indicating that HMW Ad plays an important role in regulating AMPK phosphorylation via APPL1 in 3T3-L1 adipocytes. Conclusions: HMW Ad treatment improved glucose homeostasis and resulted in reduced lipolysis, inflammation and insulin resistance in adipocytes subject to glucolipotoxicity. The beneficial modulation and regulation of APPL1 and AMPK signals by HMW Ad observed in this study represent a novel mechanism. Raising endogenous HMW Ad levels either by pharmacological or lifestyle modification could have a therapeutic value. Highlights: In vitro intricacies of HMW adiponectin (HMW Ad) in 3T3-L1 adipocytes are less studied. HMW Ad treatment improves glucose homeostasis and results in reduced lipolysis, inflammation and insulin resistance. Beneficial modulation and regulation of APPL1 and AMPK signals by HMW Ad observed in this study are a novel mechanism. Raising endogenous HMW Ad levels either by pharmacological or lifestyle modification will have a therapeutic value.